Sistem Pendukung Keputusan Promosi Jabatan Dengan Kombinasi Metode AHP dan MFEP (STMIK Budi Darma, 2022)
Management of PT.Promexx Pusat Stationery is very difficult to make decisions to assess subjective things, for ease of decision making (SPK) to determine a more precise and accurate decision. Promotion is a position according to the evaluation output during work. In the assessment of employees who get good grades, they will be promoted as a form of appreciation for employees while working in accordance with the vision and mission. In this criterion there are several assessments such as K1 (Attendance), K2 (Cooperation), K3 (Performance), K4 (Problem Solving), K5 (Ability). The purpose of this study is to help PT.Promexx Pusat Stationery make decisions about promotion of employees in the company, in this system the researcher uses the Analytical Hierarchy Process method, which is choosing a sustainable value to obtain the ratio value and to make sure the researcher has also combined the Multi Factor Evaluation Process algorithm. on choosing the final result value that will be determined in problem solving. And the result of ranking employees is the total that is obtained from the sum of all the criteria from table 14 for all candidates and will produce a total value. From this research, the highest total score is 92.01 with the first rank.